ANALYSIS OF THE QUALITY OF BULOG RICE IN THE PERSPECTIVE OF ISLAMIC ECONOMIC LAW:A STUDY IN ACEH BESAR DISTRICT, INDONESIA - Azka Amalia Jihad; Al-Ayyubi Fikramullah; Shabarullah Shabarullah (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2022)
The sale and purchase of rice carried out by BULOG Aceh Besar Regency has problems related to the quality of rice traded due to the storage of rice for too long by BULOG, causing moisture and water content of rice to damage the quality of rice, and consumers feel disadvantaged when consuming it. This research aims to find out how the policy of Bulog Aceh Besar in maintaining the stability of price of rice products marketed by farmers, and how the policy of Bulog Aceh Besar in maintaining and controlling the quality of rice in the process of stocking rice in the warehouse. The methods used are field research and library research. This type of research is a case study that is empirical law. Data collection techniques through interviews, observation, documentation and literature review. The research findings show the following: First, the policy of Perum BULOG Aceh Besar in maintaining the stability of rice product prices is carried out by purchasing grain based on HPP provisions, maintaining prices at the farm level and maintaining adequate stocks and overcoming emergencies, disasters and food insecurity. Second, BULOG Aceh Besar's policy of maintaining and controlling the quality of rice in the process of storing rice in the warehouse is carried out through integrated warehouse pest management (PHGU), promoting warehouse cleanliness, monitoring the implementation of commodity and warehouse maintenance, conducting preventive activities and curative pest control activities such as fumigation in case of pest infestation. Thirdly, the review of mabi' in Fiqh Muamalah on the system of controlling the quality and quantity of rice at BULOG Aceh Besar is in line with Islamic economic principles, where BULOG, in maintaining the quality and quantity of rice, truly considers the benefits of many ummah in times of rice scarcity by not including elements of ihtikar in the form of one group's profit only.